1994
DOI: 10.1177/107319119400100407
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Drug Users' Self-Reported HIV Risk Behaviors and Validity of Self-Reported Recent Drug Use

Abstract: This study examined the reliability and validity of the Risk Behavior Assessment, a structured interview questionnaire designed to evaluate drug use and sexual HIV risk behaviors. Participants were 218 drug users currently not in treatment who completed the RBA two times over a 48-hour period and gave urine samples on both occasions. We examined internal consistency and test-retest reliability and found that, overall, drug users reliably report drug use and sexual behavior, although the reliability of reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 334 publications
(174 citation statements)
references
References 23 publications
3
171
0
Order By: Relevance
“…We invested considerable efforts at developing a comparable interview protocol for the two cohorts, and previous studies of self-reports of street-recruited IDUs suggest that the self-reports are reasonably valid and reliable. 50,51 Nevertheless, the presence of selection, recall, or social desirability biases in the data cannot be ruled out. The mortality status of both cohorts was acquired from the same source, NDI, and we had several conversations with officials of the NDI to confirm that states followed similar reporting procedures and schedules.…”
Section: Discussionmentioning
confidence: 99%
“…We invested considerable efforts at developing a comparable interview protocol for the two cohorts, and previous studies of self-reports of street-recruited IDUs suggest that the self-reports are reasonably valid and reliable. 50,51 Nevertheless, the presence of selection, recall, or social desirability biases in the data cannot be ruled out. The mortality status of both cohorts was acquired from the same source, NDI, and we had several conversations with officials of the NDI to confirm that states followed similar reporting procedures and schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our analysis required self-reports of drug use, risk behaviours, and infection status, which may be biased by social desirability. However, self-reports of drug users have shown acceptable levels of reliability and validity (Dowling-Guyer et al, 1994;Samuels, Vlahov, Anthony, & Chaisson, 1992). Third, the potential effect of other IDUs on participants' behaviours or beliefs can modify risk behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, multicenter research on injection drug users has shown that self-report is very reliable among drug users not recruited in clinical settings. [28][29][30] Other studies 31,32 and our own [33][34][35] have found substantial operational and contextual differences among SEPs and the communities in which they operate. In California, there are potentially many important differences in both SEP characteristics and community context, and we continue to compile data that will permit in-depth analyses of these factors and HIV risk and secondary exchange.…”
Section: Discussionmentioning
confidence: 99%